EFFECT OF HYDROGEN ENRICHED DIESEL COMBUSTION ON EMISSIONS AND ENGINE PERFORMANCE AT PARTIAL LOAD CONDITIONS - Sandalci, Tarkan; Karagoz, Yasin (TURKISH SOC THERMAL SCIENCES TECHNOLOGY, 2015)
Diesel engines will be used in the following years and they are indispensable in daily life. However, stringent emission regulations force automotive manufacturers to use higher technology after-treatment devices and this causes an increase on total price of diesel engines. Also, the increase on diesel fuel prices in recent years is considered together, the researchers try to find a new fuel for diesel engines. In this study, hydrogen was introduced into intake manifold using gas injector and pilot diesel fuel was injected using diesel injectors to ignite mixture. Hydrogen energy was kept constant as 25% of total fuel and all tests were conducted at 1300 rpm constant engine speed. The effect of hydrogen addition on engine performance emissions and combustion characteristics at part loads (37%, 47% and 65%) were investigated. NOx and smoke emissions can be reduced with hydrogen addition. However, THC emission increased with hydrogen addition, CO2 and CO emissions were improved. Furthermore, peak incylinder gas pressure and peak heat release rate values were increased with hydrogen addition.
Keywords: Hydrogen; Diesel engine; Smoke; NOx; Rate of heat release; NITROGEN ADDITION; GASOLINE-ENGINE; NOX FORMATION; IGNITION; FUEL; INJECTION; GAS; SYSTEM; Thermodynamics; Engineering